2019
DOI: 10.1177/0145445519834640
|View full text |Cite
|
Sign up to set email alerts
|

Using a Multiple-Schedule Procedure to Signal the Availability of Attention: Three Demonstrations

Abstract: Adjudicated adolescents detained in residential facilities for illegal sexual behavior, as well as adolescents living at home, may engage in problem behaviors such as excessive vocalizations. In residential detention facilities, these excessive vocalizations may result in disciplinary action and loss of privileges. Moreover, excessive vocalizations may also reduce the amount of positive social interactions that staff members and caregivers have with the adolescents. The current study evaluated a multiple-sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…The present study also included an error analysis for identifying specific segments of the more complex skill that were particularly difficult for these students. This study also extends the literature on the use of behavior analytic procedures to address behavioral deficits and excesses displayed by adolescents in residential juvenile facilities (e.g., Brogan et al, ; Brogan, Falligant, & Rapp, ; Brogan, Rapp et al, ; Niedfeld et al, ).…”
Section: Discussionsupporting
confidence: 73%
“…The present study also included an error analysis for identifying specific segments of the more complex skill that were particularly difficult for these students. This study also extends the literature on the use of behavior analytic procedures to address behavioral deficits and excesses displayed by adolescents in residential juvenile facilities (e.g., Brogan et al, ; Brogan, Falligant, & Rapp, ; Brogan, Rapp et al, ; Niedfeld et al, ).…”
Section: Discussionsupporting
confidence: 73%
“…The absence of this component likely makes the procedure safer for both participants and practitioners. Finally, this study contributes to the growing body of research on the utility of behavior analytic procedures for adolescents receiving treatment in residential detention facilities (Brogan, Falligant, & Rapp, 2017;Chinnappan et al, 2019;McDougale et al, 2019;Niedfeld et al, 2019). Specifically, results of this study and those from the Neidfeld et al ( 2019) study have important clinical implications because each demonstrated that ABA practitioners could modify procedures developed for children with ASD and apply those procedures to problems displayed by adolescents in a juvenile residential facility.…”
Section: Discussionmentioning
confidence: 73%
“…Although there are situations in which students are required to tolerate delays and denials without salient signals, signaling may increase treatment efficacy and be appropriate in some situations (see Betz et al, 2013 , for one example). Niedfeld et al ( 2020 ) implemented a stimulus control procedure in which team members signaled the nonavailability and availability of staff attention for excessive vocalizations. The design of this stimulus control procedure was also informed by various studies with individuals diagnosed with ASD (e.g., Cook et al, 2014 ; Doughty et al, 2007 ; Lydon et al, 2017 ; Piazza et al, 1996 ; Rapp et al, 2009 ; Tiger et al, 2017 ).…”
Section: Behavioral Interventions For Individual Studentsmentioning
confidence: 99%
“…Niedfeld et al ( 2020 ) received referrals from dormitory staff regarding two students in the juvenile detention facility who engaged in excessive vocalizations. 7 Although the vocalizations did not necessarily contain inappropriate content, the vocalization’s frequency and duration prevented staff from completing work tasks.…”
Section: Behavioral Interventions For Individual Studentsmentioning
confidence: 99%